Practicability study of YBaCo4O7+δ and substituted samples for chemical looping air separation process - Hou, Limin; Yu, Qingbo; Wang, Kun; Wu, Tianwei; Wei, Mengqi; Yang, Fan (Environmental progress & sustainable energy, 2019)
Chemical looping air separation, producing oxygen, is a non‐traditional and energy efficient process. Oxygen carrier is core of the process. In the article, practicability of YBaCo4O7+δ and substituted samples reacting at temperature lower than 500°C as oxygen carriers are studied for a chemical looping air separation process. First, the XRD analysis of synthesized samples was performed to discern the formation of 114 phase structure. The TG results obtained by temperature‐programmed thermogravimetry show that YBaCo4O7+δ and substituted samples have high oxygen storage capacity. The DTG results obtained by isothermal and temperature‐programmed thermogravimetry show that YBaCo4O7+δ and substituted samples have a faster oxygen desorption rate and a slower oxygen absorption rate. The isothermal TG results show that the conversion time decreases, and the amount of oxygen absorption/desorption first increases and then decreases, with increasing the operating temperature of oxygen absorption. With increasing the operating temperature of oxygen desorption, the conversion time decreases. The optimal temperature of oxygen absorption and desorption is 330 and 450°C, respectively. Oxygen absorption and desorption processes occur in a highly reversible manner. © 2018 American Institute of Chemical Engineers Environ Prog, 38: 563–569, 2019